IMPROVEMENT OF SHOOTING TECHNICAL SKILLS IN THE SHOOTING RANGE WITHIN THE BIATHLON TEST FOR JUNIORS - B.-I. PELIN; C.MEREUȚĂ (Editura Universitatii Transilvania din Brasov, 2018)
: The aim of the research is to identify ways to achieve a biathlon test capacity that will favor the achievement of an optimal biological state needed to make shooting range pull more efficient. In the experimental research, the psychomotricity state is manifested through the stability of some coordinated coordinating capacities, obtained by individualized training in the field of shooting, applied by 4 junior biathlonists from CSS Dinamo Râşnov. As a result of the scientific research, we can say that the working hypothesis has been confirmed, so by individualized proprioceptive training that leads to the regulation of the biological state it is possible to optimize the technical ability of shooting in the biathlon test in the junior category.